Conservative Treatment of Hypertrophic Gingivitis - Munisovna, Khaydarova Durdona (American Journal of Bioscience and Clinical Integrity, 2025)
Hypertrophic gingivitis is an inflammatory change in the gum tissue, accompanied by its growth (hypertrophy) with the formation of pseudo-periodontal pockets covering the tooth crown. The clinical picture of hypertrophic gingivitis is characterized by swelling, burning, hyperemia and bleeding of the gums (when touched, when brushing teeth, when eating), a painful reaction to hot, cold or sour food, and an unaesthetic appearance of the gums. Diagnosis of hypertrophic gingivitis includes examination and palpation of the gums, determination of dental indices and X-ray examination. In the treatment of hypertrophic gingivitis, local anti-inflammatory therapy, sclerotherapy, physiotherapy, diathermocoagulation of gingival papillae and gingivectomy are used.